Implementasi Manajemen Syariah Pegadaian dalam Gadai Emas pada PT Pegadaian (Persero) Cabang CPS Kuala Simpang - Muhammad Faisal Alfarisyi; Zainarti Zainarti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to examine the management of Sharia Pegadaian in building consumer trust in gold pawning. This study used qualitative research methods. The data collection technique used are interview documentation studies. Data analysis uses reduction techniques, data presentation and conclusion drawing. The results of the study indicate that Sharia management at Pegadaian has been running in increasing consumer confidence in gold pawning. The evidence comes from the increasing number of consumers for gold pawning every month at the Kartini Sharia Pawnshop. Motivation and support of the Kartini Sharia Pawnshop Branch Leader makes employees feel happy and comfortable so that employee performance can be maintained to the maximum. This consumer trust can be seen from the attitudes and interests of consumers who transact at Kartini Sharia Pawnshop. In addition to gold pawning, consumers can also invest in gold, purchase motorized vehicles, pilgrimage, and pay for electricity, telephone, water and insurance at Pegadaian. Like the motto of Pegadaian overcoming problems without problems. This research is useful in providing input to maintain consumer trust in the withdrawal of consumer savings for the nearest area, especially Denpasar, especially for institutions, traders and micro and medium business owners. Therefore, it is expected that further researchers will discuss more about ways to increase consumers for gold pawns and other products in a more modern way along with the era that continues to advance.